A clinical and molecular review of inverted papilloma of the urinary tract: how to handle?. Issue 11 (11th September 2015) - Jørgensen, Peter Hjorth; Vainer, Ben; Hermann, Gregers Gautier
<x xml:space="preserve">Abstract</x> Inverted papilloma (IP) of the urinary tract is classified by the World Health Organisation as a non‐invasive urothelial tumour with normal to minimal cytological atypia of the neoplastic cells. During the 1980s, it came under suspicion of having a premalignant or malignant potential and of being concurrent with urothelial cell carcinoma (UCC). This quandary has been proven difficult to solve, due to the fact that IP is very rare and literature mostly consists of case reports with varying levels of information, making strong meta‐analyses problematic. New immunohistochemical techniques and genetic approaches are more frequently being used in the attempt to achieve better classifications, prognosis and treatment of lesions hereunder IP. This review will, in our awareness, be the first to combine the knowledge from retrospective studies with these new approaches for determining a possible premalignant potential and concurrency with UCC and subsequently outline a recommendation for follow‐up.